An Additivity Scheme for Aromaticity: The Heteroatom Case. Issue 11 (13th May 2019) - Finkelstein, Patrick; Gershoni‐Poranne, Renana
Abstract: The nucleus‐independent chemical shift (NICS)‐XY‐Scan is a simple and easy tool for the quantitative measurement of the aromaticity of polycyclic aromatic hydrocarbons and identification of the existence of local and global ring currents. We recently introduced an additivity scheme that uses the NICS‐XY‐Scans of smaller building blocks to predict the aromatic profiles of larger polycyclic aromatic hydrocarbon systems. We now report on an expansion of the methodology to include systems of varying aromatic natures containing the heteroatoms B, N, O, and S. The additivity approach allows for rapid and resource‐efficient generation of NICS‐XY‐Scans of large, complex systems. Moreover, it reveals that the magnetic criterion of aromaticity behaves in an additive manner, and that the ring currents of multi‐ring systems appear to be mostly localized within subunits of up to three rings. Abstract : Heterocyclic building blocks : Using a newly expanded set of building blocks, the aromatic profiles of polycyclic (hetero)aromatic hydrocarbons are predicted with an additivity scheme based on nucleus‐independent chemical shift (NICS)‐XY‐Scans. This approach enables simple and rapid access to the aromatic properties of complex systems and functional compounds.